2008
DOI: 10.1016/j.ajhg.2007.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypically Concordant and Discordant Monozygotic Twins Display Different DNA Copy-Number-Variation Profiles

Abstract: The exploration of copy-number variation (CNV), notably of somatic cells, is an understudied aspect of genome biology. Any differences in the genetic makeup between twins derived from the same zygote represent an irrefutable example of somatic mosaicism. We studied 19 pairs of monozygotic twins with either concordant or discordant phenotype by using two platforms for genome-wide CNV analyses and showed that CNVs exist within pairs in both groups. These findings have an impact on our views of genotypic and phen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
351
4
14

Year Published

2009
2009
2013
2013

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 532 publications
(377 citation statements)
references
References 34 publications
8
351
4
14
Order By: Relevance
“…The motivation for this study stems from our previous analysis of genetic variation and genetic heterogeneity in somatic cells, both for normal and tumor-derived samples. [15][16][17] One of our previous reports, surveying B1% of the human genome, suggested a frequent intratumoral (within the same primary tumor) heterogeneity of genetic aberrations in breast cancer. 15 We therefore hypothesized that there likely exist differences between the genetic profiles of primary tumors and corresponding metastases from the same patient.…”
Section: Introductionmentioning
confidence: 99%
“…The motivation for this study stems from our previous analysis of genetic variation and genetic heterogeneity in somatic cells, both for normal and tumor-derived samples. [15][16][17] One of our previous reports, surveying B1% of the human genome, suggested a frequent intratumoral (within the same primary tumor) heterogeneity of genetic aberrations in breast cancer. 15 We therefore hypothesized that there likely exist differences between the genetic profiles of primary tumors and corresponding metastases from the same patient.…”
Section: Introductionmentioning
confidence: 99%
“…6 However, intra-twin pair variability for germ-line CNVs could not be detected in our subset of EA and CDH MZ twins. Within the limitations of the used experimental approach, structural variants in mosaic form (above 20%) could neither be demonstrated.…”
Section: Discussionmentioning
confidence: 62%
“…Epigenetic differences have been demonstrated in MZ twins discordant for schizophrenia and in twin pairs discordant for birth weight and differences in the methylation of the COMT gene promoter region [Petronis et al, 2003;Mill et al, 2006]. Additionally, Bruder et al [2008] recently reported that MZ twin pairs who were discordant for Parkinson disease showed differences in copy number variants on genetic microarray testing. These are areas which may be of value for future exploration in NF1.…”
Section: Discussionmentioning
confidence: 99%